STRATEGI PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN INFRASTRUKTUR BERKELANJUTAN DI DESA BANYUBIRU - Retno; Hary (OECONOMICUS Journal of Economics, 2025)
Sustainable infrastructure development in the village requires active participation of the community so that the results of development not only have a short -term impact, but also can be maintained and utilized in the long run. Community involvement in infrastructure development in Banyubiru Village still faces various challenges, both from the social, economic, and institutional side. This study aims to identify obstacles and formulate effective community empowerment strategies in the development of sustainable infrastructure in Banyubiru Village, Semarang Regency. Research uses a qualitative approach with descriptive methods, and data is collected through in -depth interviews and field observations. The results showed that the main obstacles in community empowerment include overlapping development priority scale, inequality of involvement between regions, low participation due to economic pressure, lack of the role of the younger generation, and lack of social inclusiveness. The strategies implemented by the village government include formal institutional involving, capacity strengthening through training, socio-cultural approaches, utilization of mutual cooperation, and the application of sustainability principles. The conclusion of this study emphasizes the importance of building an inclusive and sustainable structure of participation, as well as the need for integration between technical and socio -cultural aspects in the process of empowering village communities. .